2012
DOI: 10.1590/s0365-05962012000300014
|View full text |Cite
|
Sign up to set email alerts
|

Sweet's syndrome: clinicopathological features of patients treated from 1997 to 2009 at Cassiano Antonio Moraes University Hospital - Vitoria (Espirito Santo)

Abstract: Sweet's syndrome or acute febrile neutrophilic dermatosis is rare in Brazil. It is clinically characterized by painful erythematous nodules, papules or plaques that occur mainly on the neck and upper limbs. Its cause may be unknown (idiopathic form) or it may be associated with malignancies, usually hematologic, or drugs. The authors describe 16 cases of the syndrome. The median age was 36 years, and all patients were white and presented solid lesions, predominantly on the upper limbs and trunk. Histopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Even though SS is also known as acute febrile neutrophilic dermatosis, our study obtained positive association with fever in only 32% of the cases, emphasising that fever is a minor criterion for SS, as pointed by Su and Liu 16 and von den Driesch. 17 Some studies obtained similar rates, 2,24,25,27 while others observed fever as a more frequent symptom in patients with SS. 26 Leukocytosis and neutrophilia were commonly observed in our cohort, which was consistent with data previously published.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Even though SS is also known as acute febrile neutrophilic dermatosis, our study obtained positive association with fever in only 32% of the cases, emphasising that fever is a minor criterion for SS, as pointed by Su and Liu 16 and von den Driesch. 17 Some studies obtained similar rates, 2,24,25,27 while others observed fever as a more frequent symptom in patients with SS. 26 Leukocytosis and neutrophilia were commonly observed in our cohort, which was consistent with data previously published.…”
Section: Discussionmentioning
confidence: 78%
“…26 Leukocytosis and neutrophilia were commonly observed in our cohort, which was consistent with data previously published. 24,27 Inflammatory tests, such as CRP and ESR, presented high values in most cases. Interestingly, we observed that malignancy was associated with higher levels of ESR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Sweet syndrome and EN exhibit several analogous clinical and histological characteristics. 11,12 Both conditions share the feature of acute onset and can be linked to similar systemic factors, including upper respiratory infections, certain medications, hematologic malignancies, and autoimmune diseases. 13,14 Both SS and EN are commonly managed with rapid initiation of glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…Sweet's syndrome and erythema nodosum share many similar clinical and histological features. 1 - 3 , 7 , 8 Both have acute onset and occur in association with many of the same systemic conditions, such as upper respiratory infections, medications, hematologic malignancies, and autoimmune disease. 2 , 5 , 8 The two conditions are responsive to similar therapeutic drugs as systemic glucocortioids or potassium iodide.…”
Section: Discussionmentioning
confidence: 99%